2017
DOI: 10.5152/npa.2017.19277
|View full text |Cite
|
Sign up to set email alerts
|

Is There any Relation Between Impaired Emotion Perception and Thought Disorder in Schizophrenia?

Abstract: Our results suggested that emotion perception disturbances could be associated with disorganised thought in schizophrenia. Impaired recognition and misinterpretation of positive emotions may contribute to the occurrence of disorganised thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Moreover, Schneider et al ( 21 ) found that patients could not distinguish between happy and sad facial expressions and they improperly identified the target emotion as sad. Patients in this study also showed a lack of recognition of happy facial expressions compared with healthy people; Hargreaves et al ( 22 ) and Yildirim et al ( 16 ) arrive at a similar conclusion.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Moreover, Schneider et al ( 21 ) found that patients could not distinguish between happy and sad facial expressions and they improperly identified the target emotion as sad. Patients in this study also showed a lack of recognition of happy facial expressions compared with healthy people; Hargreaves et al ( 22 ) and Yildirim et al ( 16 ) arrive at a similar conclusion.…”
Section: Resultssupporting
confidence: 81%
“…Eleven studies investigated hospitalized patients ( 18 , 21 , 25 , 26 , 30 , 31 , 38 , 39 , 45 , 47 , 49 ). Eleven studies surveyed outpatients ( 14 16 , 20 , 27 , 32 35 , 37 , 40 ). Seven papers examined both inpatients and outpatients ( 9 , 17 , 22 , 24 , 44 , 48 , 50 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, severity of negative FTD was also predicted by an increased gray matter volume in the prefrontal regions and dorsal anterior cingulate cortex. Social cognitive impairments and symptoms of schizophrenia are reported to correlate with abnormal over-activation of the posterior temporal cortex and temporo-parietal occipital junction, related to self-processing and face recognition ( Yildirim et al, 2017 ). In addition, patients with schizophrenia exhibited increased misrecognition of facial emotions that correlated with disorganized thought, suggesting that the inaccurate or disorganized representation of another person’s mental or emotional state disrupts the integration of external contextual information and internal emotional representations.…”
Section: Transitive 3-4mentioning
confidence: 99%
“…Individuals with this disorder has a range of symptoms that include disturbances in content of thought, form of thought, perception, affect, sense PEOPLE: International Journal of Social Sciences ISSN 2454-5899 of self, motivation, behavior, and interpersonal functioning. Consequently, they exhibit social cognitive impairment (Yildirim, et al 2018).…”
Section: Introductionmentioning
confidence: 99%